1994
DOI: 10.1037/0003-066x.49.6.493
|View full text |Cite
|
Sign up to set email alerts
|

What we know about leadership: Effectiveness and personality.

Abstract: Although psychologists know a great deal about leadership, persons who make decisions about real leaders seem largely to ignore their accumulated wisdom. In an effort to make past research more accessible, interpretable, and relevant to decision makers, this article defines leadership and then answers nine questions that routinely come up when practical decisions are made about leadership (e.g., whom to appoint, how to evaluate them, when to terminate them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
708
3
27

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 944 publications
(747 citation statements)
references
References 56 publications
9
708
3
27
Order By: Relevance
“…(The data are not yet in on whether some degree of self-enhancement, accompanied by "positive illusions" [ Taylor & Brown, 1988 ] that foster hope and effort, is adaptive.) Studies of leadership (summarized in Hogan, Curphy, & Hogan, 1994 ) similarly have found that leaders who are narcissistic (characterized by traits such as arrogance, vindictiveness, and selfishness) tend to fail despite the presence of other traits typically associated with good leadership, such as intelligence, perseverance, and ambition. Interestingly, these leaders are difficult to detect by self-report, because they present themselves as confident and high in self-esteem.…”
Section: Other Studies Documenting Unconscious Emotional Processesmentioning
confidence: 99%
“…(The data are not yet in on whether some degree of self-enhancement, accompanied by "positive illusions" [ Taylor & Brown, 1988 ] that foster hope and effort, is adaptive.) Studies of leadership (summarized in Hogan, Curphy, & Hogan, 1994 ) similarly have found that leaders who are narcissistic (characterized by traits such as arrogance, vindictiveness, and selfishness) tend to fail despite the presence of other traits typically associated with good leadership, such as intelligence, perseverance, and ambition. Interestingly, these leaders are difficult to detect by self-report, because they present themselves as confident and high in self-esteem.…”
Section: Other Studies Documenting Unconscious Emotional Processesmentioning
confidence: 99%
“…Multiple theories of leadership have also cited the critical role of trust. For example, theories have suggested that charismatic leaders build trust in their followers (Kirpatrick & Locke, 1996;Shamir, Zakay, Breinen, & Popper, 1998), that integrity or trustworthiness is an important trait of leaders (Bass, 1990), that trust is a core basis of effective leadership (Bennis & Nanus, 1985;Fairholm, 1994;Zand, 1997), and that trust is central in subordinates' perceptions of effective leadership (Hogan, Curphy, & Hogan, 1994). Lastly, a number of management practices, such as leadership development programs, recognize the importance of trust to varying degrees (e.g., Conger, 1992;Peterson & Hicks, 1996).…”
Section: The Effect Of Trust In Leadership On Team Performancementioning
confidence: 99%
“…Despite some known limits (Eysenck, 1991;Paunonen & Jackson, 2000), over the last 50 years the Big Five model has become a standard in psychology and experiments using the Big Five have shown that personality traits influence many aspects of task-related individual behaviour. For example, the success of most interpersonal tasks depends on the personalities of the participants, and personality traits influence leadership ability (Hogan, Curphy, & Hogan, 1994), general job performance (Furnham, Jackson, & Miller, 1999), attitude toward machines (Sigurdsson, 1991), sales ability , teacher effectiveness (Rushton, Murray, & Erdle, 1987), and academic ability and motivation (Furnham & Mitchell, 1991;Komarraju & Karau, 2005). However, to date there has been little work on the automatic recognition of personality traits (Argamon, Dhawle, Koppel, & Pennebaker, 2005;Mairesse & Walker, 2006a, 2006bOberlander & Nowson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of leaders using personality dimensions could be useful in analysing meetings and the conversations of suspected terrorists (Hogan et al, 1994;Tucker & Whittaker, 2004;Nunn, 2005). Dating websites could analyse text messages to try to match personalities and increase the chances of a successful relationship (Donnellan, Conger, & Bryant, 2004).…”
Section: Introductionmentioning
confidence: 99%